Energy Harvesting from Traffic-Induced Vibrations Using Piezoelectric Materials (International Journal of Environmental Sciences, 2025)
This paper investigates how piezoelectric materials can be applied to capture and convert kinetic energy from traffic vibrations into electricity for sustainable energy harvesting. The goal is to analyze available literature from the years 2000-2021, design a system, and assess the feasibility of energy conversion through electromechanical stress. The methodology consists of exhaustive piezoelectric materials and harvester configurations surveys. This research shows that although there are challenges related to power output, optimized design and material selection can facilitate electricity generation for low-power roadside applications. The study also demonstrates enhanced sustainability and self-sufficient infrastructure with the promising prospect of decentralized energy resources in smart cities.